Explaining Concept of Smart Power and Identifying Its Components in Universities of Medical Sciences: A Qualitative Study - Elham Shakiba; Mahboobeh Sadat Fadavi; Mohammad Ali Nadi (پیاورد سلامت)
Background and Aim: Smart power is the solidarity between science, knowledge and communication. With the advancement of technology, new space has been created in medical sciences. The aim of this research is Explaining the concept of Smart power and identifying its components in Universities of Medical Sciences Materials and Methods: The current research was done qualitatively in 2023 using the grounded theory method. Deep and semi-structured interview was done with 13 faculty members of Medical Sciences Universities of the country selected through the purposeful and snowball sampling method and reached theoretical saturation. Strauss -Corbin method based on open, axial and selective coding was used for data analysis. To determine the accuracy and validity of the data, after coding the data, the opinions of six interview participants and six university professors who were familiar with the subject and method of the present research were sought. Results: After the initial concepts were formulated, 77 open codes, 15 core codes, and five selective codes were identified for smart power. Strengthening artificial intelligence, e-health transformation, cross-border activities together constitute health technological responsiveness, are causal factors that affect the phenomenon of smart power. Actions that should be taken for smart power in medical universities, as strategies include technological innovation that is carried out with systematic technology, technological education, and research capacity building. Cyber ​​management with technology-based performance, communication capability enhancement, information management are contextual factors that create special conditions for effective strategies. The conflict between tradition and modernization, information anxiety as organizational risks are intervention factors that interfere with and limit strategies. If the special conditions of strategies are provided and intervention factors are controlled, the outcome of strategies will be technological progress, development of communication network, integration of hard and soft power, and overall comprehensive health. Conclusion: Using and developing this power, the policy makers of the health system will be able to solve problems such as the non-uniformity of health facilities in different regions, also the use of virtual university and electronic education, which will remove the time and place limitations and provide the opportunity for education to applicants in different parts of the country.